Exploring Critical Approaches to Historical Analysis: A Comprehensive Assessment of Tārīkh al-Khulafā’ by Jalal al-Dīn ‘Abd al-Raḥmān al-Ṣuyūṭī - Bilal, Bilal Saeed (Journal of Islamic History and Manuscript, 2024)
This paper explores the role of criticism in historical research, emphasizing the careful evaluation of historical evidence to assess reliability. By examining both primary and secondary sources, this paper delves into the intricacies of critical analysis, focusing on the distinction between external and internal criticism. External criticism assesses the authenticity and origin of a document, examining factors such as authorship, date, and context to ensure its genuineness. On the other hand, internal criticism involves content analysis, interpreting the meaning behind the text, and evaluating the author’s intent, biases, and reliability. The paper uses the historical source Tārīkh al-Khulafā’ by Jalal al-Dīn ‘Abd al-Raḥmān al-Ṣuyūṭī, a prominent 10th-century Islamic scholar, as a case study to illustrate these critical approaches. Through a thorough examination of al-Ṣuyūṭī’s work, the paper highlights the significance of understanding the broader implications of historical narratives while also scrutinizing the specific content for accuracy and intent. The critical evaluation of Tārīkh al-Khulafā’ reveals the complexities involved in historical research, showcasing how historians can navigate biases, omissions, and the reliability of sources to construct accurate historical narratives. This study clarifies its theoretical aspects by providing a comprehensive understanding of historical research criticism. It demonstrates its practical application, underscoring its essential function in ensuring the integrity and accuracy of historical inquiry.